DETERMINANTS OF PROFITABILITY IN INDONESIAN NON-FINANCIAL COMPANIES (2012–2023) - Muhammad Zakaria; Valentino Budhidharma (UPT Publikasi Ilmiah UNISBA, 2025)
This study investigates the determinants of profitability among Indonesian non-financial companies from 2012 to 2023, focusing on ROA and ROE. Using GMM to address endogeneity and machine learning models (Random Forest and XGBoost) for variable importance analysis, it identifies key factors influencing profitability. Company age often introduces inefficiencies and structural rigidity, reducing profitability, while high labor costs erode margins in labor-intensive industries. In contrast, increased capital intensity boosts profitability through investments in technology and infrastructure. Economic growth supports profitability by expanding purchasing power, whereas inflation raises costs and limits spending. Effective cost management, innovation, and strategic adaptability are crucial for sustaining profitability, while liquidity and market concentration are contextually relevant. Companies prioritizing innovation, cost control, and agility are better positioned to maintain profitability. Additionally, fostering innovation, simplifying structures, and enhancing agility address challenges of aging firms, while efficient workforce management and automation mitigate high labor costs. This study is limited by its focus on Indonesian non-financial companies and the use of secondary data, which may affect generalizability. Future research should expand to other emerging markets, explore sector-specific dynamics, and incorporate factors such as corporate governance and sustainability practices to provide broader insights into profitability drivers.